ANALISISA DIGITAL MARKETING “NGE LIVE YUK” TERHADAP PENJUALAN PRODUK UMKM TINJAUAN MENGGUNAKAN METODE SYSTEMATIC LITERATURE REVIEW - Edi Santoso; Joy Nashar Utamajaya (CV. ALIM'SPUBLISHING, 2025)
This study uses the Systematic Literature Review (SLR) method to analyze the effect of digital marketing on the sales growth of Micro, Small and Medium Enterprises (MSMEs). From a review of 19 articles published between 2019 and 2024, this study consistently shows that digital marketing strategies, such as the use of social media platforms and other digital marketing techniques, play an important role in increasing brand awareness, consumer interaction, and sales conversions of MSMEs. Optimization of information technology infrastructure has also been proven to increase the effectiveness of digital marketing strategies in MSMEs. These findings have significant implications for industry players and parties related to MSMEs, emphasizing the importance of strategic implementation and management of digital marketing for sustainable business growth and competitive advantage in today's digital era.